Invasive Scedosporium and Lomentospora prolificans Infections in Australia: A Multicenter Retrospective Cohort Study. (8th February 2023) - Neoh, Chin Fen; Chen, Sharon C A; Crowe, Amy; Hamilton, Kate; Nguyen, Quoc A; Marriott, Debbie; Trubiano, Jason A; Spelman, Tim; Kong, David C M; Slavin, Monica A
Abstract: Background: Management of Scedosporium/Lomentospora prolificans infections remains challenging. We described predisposing factors, clinical manifestations, and outcomes of these rare mold infections, including predictors of early (1-month) and late (18-month) all-cause mortality and treatment failure. Methods: We conducted a retrospective Australian-based observational study of proven/probable Scedosporium/L prolificans infections from 2005 to 2021. Data on patient comorbidities, predisposing factors, clinical manifestations, treatment, and outcomes up to 18 months were collected. Treatment responses and death causality were adjudicated. Subgroup analyses, multivariable Cox regression, and logistic regression were performed. Results: Of 61 infection episodes, 37 (60.7%) were attributable to L prolificans . Forty-five of 61 (73.8%) were proven invasive fungal diseases (IFDs), and 29 of 61 (47.5%) were disseminated. Prolonged neutropenia and receipt of immunosuppressant agents were documented in 27 of 61 (44.3%) and 49 of 61 (80.3%) episodes, respectively. Voriconazole/terbinafine was administered in 30 of 31 (96.8%) L prolificans infections, and voriconazole alone was prescribed for 15 of 24 (62.5%) Scedosporium spp infections. Adjunctive surgery was performed in 27 of 61 (44.3%) episodes. Median time to death post–IFD diagnosis was 9.0 days, and only 22 of 61 (36.1%) attained treatment success at 18 months. Those who survived beyond 28 days of antifungal therapy were less immunosuppressed with fewer disseminated infections (both P < .001). Disseminated infection and hematopoietic stem cell transplant were associated with increased early and late mortality rates. Adjunctive surgery was associated with lower early and late mortality rates by 84.0% and 72.0%, respectively, and decreased odds of 1-month treatment failure by 87.0%. Conclusions: Outcomes associated with Scedosporium/L prolificans infections is poor, particularly with L prolificans infections or in the highly immunosuppressed population. Abstract : Higher rates of mortality and treatment failure were observed in Lomentospora prolificans infections or in the highly immunosuppressed patients with hematological malignancy or hematopoietic stem cell transplant. Adjunctive surgery was associated with lower mortality and decreased odds of 1-month treatment failure.